Good girls lie - Ellison, J. T (Mira, 2019)
Perched atop a hill in the tiny town of Marchburg, Virginia, The Goode School is a prestigious prep school known as a Silent Ivy. The boarding school of choice for daughters of the rich and influential, it accepts only the best and the brightest. Its elite status, long-held traditions and honor code are ideal for preparing exceptional young women for brilliant futures at Ivy League universities and beyond. But a stranger has come to Goode, and this ivy has turned poisonous. In a world where appearances are everything, as long as students pretend to follow the rules, no one questions the cruelties of the secret societies or the dubious behavior of the privileged young women who expect to get away with murder. When a popular student is found dead, the truth cannot be ignored. Rumors suggest she was struggling with a secret that drove her to suicide. But look closely<U+2026>because there are truths and there are lies, and then there is everything that really happened.